Halal Product Uniqueness on Marketing Performance: The Role of Islamic Market Orientation and Islamic Innovativeness - Nurudin, Nurudin; Muyassarah, Muyassarah; Kalimah, Siti (Universitas Muhammadiyah Magelang, 2024)
This study is a empirical investigation aimed at exploring the impact of Islamic market orientation, Islamic innovativeness, and halal product uniqueness on marketing performance. The sample for this study consisted of 180 executives from the food processing sector in Central Java, Indonesia. Utilizing Structural Equation Modeling (SEM), the data was analyzed. The results reveal that Islamic innovativeness is positively and significantly influenced by Islamic market orientation. Furthermore, Islamic market orientation exerts a positive and significant impact on halal product uniqueness. Likewise, Islamic innovativeness demonstrates a positive and significant effect on halal product uniqueness. Collectively, Islamic market orientation, Islamic innovativeness, and halal product uniqueness exhibit a positive and significant influence on marketing performance. The analysis of indirect effects indicates that Islamic innovativeness and halal product uniqueness can act as mediators in the relationship between Islamic market orientation and marketing performance.